MODEL LOYALITAS PELANGGAN PADA PERBANKAN MIKRO: PERCEIVED RISK SEBAGAI VARIABEL MODERASI - Suliyanto Suliyanto; Pramono Hari Adi; Eling Purwanto Jati (Jurnal Keuangan dan Perbankan, 2012)
The purpose of this study was to analyze the effect of relationship marketing on customer satisfaction andswitching cost, to analyze the effect of cutomer satisfaction, relationship marketing and switching cost on customerloyalty, and to analyze percieved risk as a moderation variable on causal relationship between cutomersatisfaction, relationship marketing and switching cost on customer loyalty. The samples were mikro bankingconsumers in Banyumas, Cilacap, Purbalingga and Banjarnegara. The sample size in this study were 120respondents. Sampling was done by purposive sampling method. Analytical tool used were the sub-group regressionanalysis and Chow test.The results of this study were that relationship marketing had positive effect oncustomer satisfaction and switching cost, cutomer satisfaction, relationship marketing and switching cost hadpositive effect on customer loyalty and, percieved risk moderated the relationship between cutomer satisfaction,relationship marketing and switching cost on customer loyalty.